Evaluating the Individual Criminal Responsibility of Gukurahundi Perpetrators under International Law - Malunga, Siphosami (Comparative and International Law Journal of Southern Africa)
The aim of this article is to evaluate whether individual criminal responsibility (ICR) is attributable to perpetrators of the Gukurahundi atrocities committed in Matabeleland and Midlands, Zimbabwe, between 1983 and 1987. The criminal liability of Gukurahundi perpetrators is evaluated against the legal requirements garnered from conventions, jurisprudence of international criminal tribunals and the work of leading scholars. Firstly, the article provides an overview and historical development of the concept of ICR under international law. Second, it examines the theories of criminality under international law. Third, it analyses the forms and modalities of ICR including relevant specific crimes. Fourth, it evaluates the individual and superior responsibility of Gukurahundi perpetrators. A crucial feature of international criminal law is the legal obligation to investigate, prosecute and punish perpetrators of international crimes. The article therefore explores the different ways in which ICR could be attributed to perpetrators of the Gukurahundi international crimes. The author sets out to advance knowledge and understanding of possible mechanisms to hold perpetrators of the Gukurahundi atrocities criminally accountable under international law.